Studies in the Rhamnaceae, III a Taxonomic Revision of Indian Ventilagineae - Banerjee, S. P.; Mukerjee, P. K. (Indian Forester, 1970)
Ventilagineae, a tribe under Rhamnaceae has about 47 species (Suessenguth, 1953), scattered over the tropics of Asia, Africa, Australia and the Polynesian islands. The area taken up for this revision is India, including the Andaman and Nicobar group of islands. This tribe includes two closely related genera: Smythea Seem. ex A. Gray and Ventilago Gaertn., mainly distinguishable on a single character, viz., the nature of the fruit. Four species and a variety of Ventilago and four species of Smythea have been described here from the area under study. Efforts have been made to give full descriptions with synonymy of the taxa treated here along with critical notes and workable keys to facilitate correct identity.